2016
DOI: 10.5194/acp-16-1511-2016
|View full text |Cite
|
Sign up to set email alerts
|

Origin of oxidized mercury in the summertime free troposphere over the southeastern US

Abstract: Abstract. We collected mercury observations as part of the Nitrogen, Oxidants, Mercury, and Aerosol Distributions, Sources, and Sinks (NOMADSS) aircraft campaign over the southeastern US between 1 June and 15 July 2013. We use the GEOS-Chem chemical transport model to interpret these observations and place new constraints on bromine radical initiated mercury oxidation chemistry in the free troposphere. We find that the model reproduces the observed mean concentration of total atmospheric mercury (THg) (observa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
96
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 73 publications
(112 citation statements)
references
References 81 publications
12
96
1
Order By: Relevance
“…A combination of ETMEP and CARIBIC observations over Germany resulted in a uniform TM and GEM distribution in the free troposphere during summer and TM concentrations close to those measured at ground level were found on six overflights of the CARIBIC aircraft in April, June, and September. A similar vertical dis- tribution was found in North America during winter (Brooks et al, 2014) and summer Gratz et al, 2015;Shah et al, 2016). In none of these cases a substantial TM gradient was found inside the free troposphere and the GEM / TM ratio was in the range of 0.95-0.99 in the upper free troposphere, which is a ratio typically found inside the PBL.…”
Section: Resultssupporting
confidence: 50%
See 3 more Smart Citations
“…A combination of ETMEP and CARIBIC observations over Germany resulted in a uniform TM and GEM distribution in the free troposphere during summer and TM concentrations close to those measured at ground level were found on six overflights of the CARIBIC aircraft in April, June, and September. A similar vertical dis- tribution was found in North America during winter (Brooks et al, 2014) and summer Gratz et al, 2015;Shah et al, 2016). In none of these cases a substantial TM gradient was found inside the free troposphere and the GEM / TM ratio was in the range of 0.95-0.99 in the upper free troposphere, which is a ratio typically found inside the PBL.…”
Section: Resultssupporting
confidence: 50%
“…While gaseous elemental mercury (GEM) makes up the vast majority of total atmospheric mercury near the surface (Sprovieri et al, 2016 this issue), recent aircraft-based observations have indicated that there is significant oxidation of mercury occurring in the free troposphere (FT) (Brooks et al, 2014;Lyman and Jaffe, 2012;Jaffe et al, 2014;Gratz et al, 2015;Shah et al, 2016). However, apart from GEM no individual mercury compound has been identified so far and the atmospheric oxidized mercury is an unknown mixture of mercury bound to Br, Cl, OH, O, and NO 2 compounds .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In BRCHEM1 the underestimation is evident (ratio BRCHEM1 / observations 0.77) while in BRCHEM2 the model results and observations are closer (ratio 0.90). Thus, increasing the Br concentration gives model results closer to observations, as shown also in Shah et al (2016), who tripled the Br and BrO concentrations in GEOS-CHEM model (with respect to Parrella et al, 2012, where an underestimation of 30 % was found for BrO concentrations compared to the global mean obtained by satellite observations) to model the NOMADSS field campaign (Gratz et al, 2015). Differently to the Shah et al (2016) study, RGM reduction is not implemented here; for the purposes of this paper it was necessary to standardise the experiments as far as possible.…”
Section: Mercury Oxidationmentioning
confidence: 62%